New phenomena of photo-luminescence and persistent luminescence of a Eu2+, Tb3+ codoped Ca6BaP4O17 phosphor under high hydrostatic pressure. Issue 24 (12th June 2020) - Guo, Haijie; Seto, Takatoshi; Geng, Ting; Zou, Bo; Li, Guangshe; Uwatoko, Yoshiya; Tang, Zuobin; Li, Zebin; Wang, Yuhua
Abstract : The possibility of regulating the photo luminescence and persistent luminescence performances of Ca6 BaP4 O17 :Eu 2+, Tb 3+ under high hydrostatic pressure. Abstract : In this study, we present a photo-luminescence (PL) and persistent luminescence (PersL) investigation of Ca6 BaP4 O17 :Eu 2+, Tb 3+ (CBPO:Eu, Tb) at high hydrostatic pressure in the range of 0–11.04 GPa. More importantly, there is a significant increase of PL intensity and extension of PersL duration time at a pressure point of ∼0.15 GPa.